A randomized phase II feasibility trial of a multimodal intervention for the management of cachexia in lung and pancreatic cancer. Issue 5 (14th June 2017) - Solheim, Tora S.; Laird, Barry J.A.; Balstad, Trude Rakel; Stene, Guro B.; Bye, Asta; Johns, Neil; Pettersen, Caroline H.; Fallon, Marie; Fayers, Peter; Fearon, Kenneth; Kaasa, Stein
Abstract: Background: Cancer cachexia is a syndrome of weight loss (including muscle and fat), anorexia, and decreased physical function. It has been suggested that the optimal treatment for cachexia should be a multimodal intervention. The primary aim of this study was to examine the feasibility and safety of a multimodal intervention (n‐3 polyunsaturated fatty acid nutritional supplements, exercise, and anti‐inflammatory medication: celecoxib) for cancer cachexia in patients with incurable lung or pancreatic cancer, undergoing chemotherapy. Methods: Patients receiving two cycles of standard chemotherapy were randomized to either the multimodal cachexia intervention or standard care. Primary outcome measures were feasibility assessed by recruitment, attrition, and compliance with intervention (>50% of components in >50% of patients). Key secondary outcomes were change in weight, muscle mass, physical activity, safety, and survival. Results: Three hundred and ninety‐nine were screened resulting in 46 patients recruited (11.5%). Twenty five patients were randomized to the treatment and 21 as controls. Forty‐one completed the study (attrition rate 11%). Compliance to the individual components of the intervention was 76% for celecoxib, 60% for exercise, and 48% for nutritional supplements. As expected from the sample size, there was no statistically significant effect on physical activity or muscle mass. There were no intervention‐related Serious Adverse Events and survival was similar between the groups. Conclusions: A multimodal cachexia intervention is feasible and safe in patients with incurable lung or pancreatic cancer; however, compliance to nutritional supplements was suboptimal. A phase III study is now underway to assess fully the effect of the intervention.